Ábrándok és remények: Gelencsér András Ábrándok bűvöletében című könyvének továbbgondolása - Halász, László (Kultúratudományi Szemle, 2024)
Dreams and Hopes. Reflecting on András Gelencsér's book Under the Spell of Illusions András Gelencsér's study analyses the depletion of the Earth's raw material resources and concludes that it makes the functioning of modern societies unsustainable in its present form. The problems and opportunities—or rather the lacks of them—examined in depth in the Study have resulted in a pessimistic scenario for the future. A rethinking of the problems raised by the Study, on the basis of the information currently available, offers the possibility of developing an optimistic scenario which is not less plausible than the pessimistic one. I shall show that the raw materials problem is in fact an energy problem and put the predictions of the Study into a time frame. I shall state the unconditional imperative of energy supply, the violation of which would fundamentally threaten the functioning of society.